PENGARUH KOMPETENSI DAN KEPRIBADIAN TERHADAP KINERJA GURU DENGAN MEDIASI KOMITMEN GURU (Students' Journal of Economic and Management, 2013)
The purpose of this research was analyze the enfluence of teachers’ competence and personality towards teacher performance through mediation of teachers’ commitment. The population  of this research were 212 teachers and the samples were 139 teachers  of Government Yunior High School in Pati Regency, Juwana District. Data was gathered by giving questionnaire to the respondent using a samples method. The research proved that the ability of model to explain the influence of teachers’ competence and personality toward teacher’ commitment was 66,7 % , while to explain the enfluence of the tree variables all together toward teacher’s performance was 61,9 %. For data operation, SPSS 16.0 version was used. The result are the first hypothesis (H1) “Teacher Competence has positive and significant effect on Teachers’ Commitment means that higher influence of  Competence , will make higher of it (H2) “Personality  has a positive and significant effect on Teachers’ Commitment means that higher influence of  personality, will make higher of it. In the third hypothesis (H3) “ Teachers Competence has positive and significant impact on teachers performance, means that the higher influence of it, the higher performance caused” Fourth hypothesis (H4) “Personality has positive and significant effect on prerformance of teacher means the higher the of it will improve teacher performance. The Fifth hypothesis (H5) Teachers’ Commitment has positive influence on performance means that the higher it will have influence the higher performance caused.  The Sixth hypothesis (H6) Teachers’ Commitment  has not positive  mediated influence competence toward teacher performance. (H7) Teachers’ Commitment  has not positive mediated influence personality toward teacher performance.   Keyword : teacher competencies, personality, teacher commitment and teacher performance